LINGUISTIC FEATURES IN SUICIDE NOTE OF ALAMGIR KHAN TAREEN: FORENSIC STYLISTIC ANALYSIS - Yolanda Azhari Herman; Salsabilla Aivira; Miftahul Jannah; Khusnul Khotimah; Risky Aditya Dwitama Selian; Rahmadsyah Rangkuti (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas Balikpapan, 2023)
This study delves into the linguistic features uncovered in suicide notes, focusing on the case of Alamgir Khan Tareen. Employing a qualitative approach with a basis in qualitative content analysis, the research seeks to comprehend these features from the perspective of the victims. The study specifically analyzes the content of publicly accessible suicide notes from well-known individuals, collected from Twitter. Employing a three-step reading, describing, and classifying method, the linguistic features identified include clear reasoning, expressing emotion, text structure, grammar, and punctuation. The analysis of Tareen's suicide note demonstrates the presence of these characteristics, shedding light on the motivations and psychological state of the victim. Notably, the linguistic features, particularly clear reasoning, and expressing emotion unveil the intricate interplay of personal struggles and health-related issues in Tareen's decision to end his life. Understanding such linguistic features holds significant implications for suicide prevention and mental health awareness.